County-level barriers in the COVID-19 vaccine coverage index and their associations with willingness to receive the COVID-19 vaccine across racial/ethnic groups in the U.S. - Fernandez, Jessica R.; Strassle, Paula D.; Richmond, Jennifer; Mays, Vickie M.; Forde, Allana T. (Frontiers in Public Health, 2023)
Background County-level vaccination barriers (sociodemographic barriers, limited healthcare system resources, healthcare accessibility barriers, irregular healthcare seeking behaviors, history of low vaccination) may partially explain COVID-19 vaccination intentions among U.S. adults. This study examined whether county-level vaccination barriers varied across racial/ethnic groups in the U.S. and were associated with willingness to receive the COVID-19 vaccine. In addition, this study assessed whether these associations differed across racial/ethnic groups. Methods This study used data from the REACH-US study, a large online survey of U.S. adults (N = 5,475) completed from January 2021-March 2021. County-level vaccination barriers were measured using the COVID-19 Vaccine Coverage Index. Ordinal logistic regression estimated associations between race/ethnicity and county-level vaccination barriers and between county-level vaccination barriers and willingness to receive the COVID-19 vaccine. Models adjusted for covariates (age, gender, income, education, political ideology, health insurance, high-risk chronic health condition). Multigroup analysis estimated whether associations between barriers and willingness to receive the COVID-19 vaccine differed across racial/ethnic groups. Results American Indian/Alaska Native, Black/African American, Hispanic/Latino ELP [English Language Preference (ELP); Spanish Language Preference (SLP)], and Multiracial adults were more likely than White adults to live in counties with higher overall county-level vaccination barriers [Adjusted Odd Ratios (AORs):1.63–3.81]. Higher county-level vaccination barriers were generally associated with less willingness to receive the COVID-19 vaccine, yet associations were attenuated after adjusting for covariates. Trends differed across barriers and racial/ethnic groups. Higher sociodemographic barriers were associated with less willingness to receive the COVID-19 vaccine (AOR:0.78, 95% CI:0.64–0.94), whereas higher irregular care-seeking behavior was associated with greater willingness to receive the vaccine (AOR:1.20, 95% CI:1.04–1.39). Greater history of low vaccination was associated with less willingness to receive the COVID-19 vaccine among Black/African American adults (AOR:0.55, 95% CI:0.37–0.84), but greater willingness to receive the vaccine among American Indian/Alaska Native and Hispanic/Latino ELP adults (AOR:1.90, 95% CI:1.10–3.28; AOR:1.85, 95% CI:1.14–3.01). Discussion Future public health emergency vaccination programs should include planning and coverage efforts that account for structural barriers to preventive healthcare and their intersection with sociodemographic factors. Addressing structural barriers to COVID-19 treatment and preventive services is essential for reducing morbidity and mortality in future infectious disease outbreaks.